Lifelong Learning: A Landmark for Personal Development and New Opportunities for Modernization of a University Library - Daribayeva, Gulshat; Utebaliyeva, Perizat (7th International Conference on Emerging Global Trends in University Library Development (Library Connect 2018), 2018)
The article is devoted to the role of the university library in supporting and developing lifelong education for different segments of society. The practical experience of the information-resource center American Corner and Maker Space Astana, located in the Eurasian National University Library, shows the importance of supporting personal growth and skill development of users. Considering the functioning “American Corner and Maker Space Astana” as one of the modern phenomena of social development, the authors of the article suggest looking at its experience in organizing all of its activities. This article will analyze activities, the survey results of users, the results of observations, as well as the success stories that have influenced the personal growth and success of its visitors (teachers, students and other categories of users).
Keywords: lifelong education; university library; maker space zone; open access; Kazakhstan